PERAN EPISTEMOLOGI DALAM PENGEMBANGAN PENGETAHUAN PENDIDIKAN: IMPLIKASINYA TERHADAP PEMBELAJARAN MENDALAM DAN PENELITIAN PENDIDIKAN - Endah Widyati; Hasmitawati; Hendri Budiman; Retno Wahyu Ningsih; Saukani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Epistemology is a branch of philosophy that examines the nature, sources, validity, and limitations of human knowledge. In education, epistemology provides a philosophical foundation for the development and validation of educational knowledge. This study aims to analyze the role of epistemology in educational knowledge development, identify the sources and criteria of scientific knowledge, explore major epistemological paradigms, and examine their relevance to Deep Learning and educational research. Using a library research approach, data were collected from books, scientific journals, and other relevant academic sources and analyzed through descriptive qualitative methods. The findings show that educational knowledge originates from empirical experience, reason, intuition, authority, and revelation. Scientific knowledge in education must meet the criteria of rationality, objectivity, empiricism, systematic organization, verifiability, and communicability. Furthermore, epistemological paradigms, including empiricism, rationalism, criticism, and constructivism, have significantly influenced learning theories and research methodologies. The study also reveals that Deep Learning aligns closely with constructivist epistemology, emphasizing learners’ active role in constructing knowledge through meaningful, mindful, and joyful learning experiences. Therefore, understanding epistemology is essential for educators and researchers in producing valid, relevant, and accountable educational knowledge and supporting the implementation of Deep Learning in contemporary education.